STUDI USAHATANI JAGUNG DAN HORTIKULTURA PADA PETANI DI KAMPUNG SUMBER BOGA DISTRIK MASNI (STUDY OF CORN AND HORTICULTURE OF FARMERS IN SUMBER BOGA VILLAGE MASNI DISTRICT) - Fitriyani; Meky Sagrim; Siti Halimatus Sa'adiyah (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2020)
Approximately two years the farmer who moved in cultivating the types of corn and horticultural commodities from those cultivated before, namely rice in Sumber village. This study aims to examine the production of corn and horticulture farming in the village of Sumber Boga, Masni District. Respondents were determined using a random sample method of switching farmers as many as 30 respondents from approximately 80 farmers who switched (37.5%). Methods of data analysis obtained in this study were processed tabulation. is an analysis of production, income, revenue, and cost calculations. The results showed that the farming branches that gave the greatest contribution to the income of farmers in Sumber Boga village were large red chilies (27%), tomatoes (12%), long beans (9%) and beans (15%).